FUNCTIONAL REACH TEST DI POSYANDU KUNTUM MELATI DESA MALANGJIWAN - Prayitno, Dedi; Rofiatun, Rofiatun; Jumiati, Jinten; Naima, Aisyah Lifsantin (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Data information on active elderly people in Indonesia in 2020 is 9.78% of Indonesia's population of 270.20 people. The category of elderly population growth increased by around 7.59% when compared with 2010 data, the increase in the number of elderly people coincided with an increase in elderly balance disorders. At this stage a person experiences several changes, both mental and physical changes. Normal changes in the aging process such as physical appearance, in the form of graying hair, wrinkles on the face, and disturbances in the five senses, as well as decreased endurance. Parameters and physical ability tests are carried out using the function reach test. Static balance measurement can be done with the functional reach test. This test measures the subject's reaching power when standing with his arms extended forward. The observation results were based on data obtained from 32 elderly participants who attended, namely 7 were good and 25 were poor according to the existing reference value, vital signs where the average blood pressure was 140/100 mmHg.